DIRECTIONAL VARIABILITY OF FUNDUS REFLECTANCE IN ACUTE MACULAR NEURORETINOPATHY: EVIDENCE FOR A CONTRIBUTION OF THE STILES–CRAWFORD EFFECT. (2018) - Bottin, Caroline; Grieve, Kate; Rossant, Florence; Pedinielli, Alexandre; Mrejen, Sarah; Paques, Michel
Abstract : Purpose: To document directional reflectivity of fundus lesions in a case of acute macular neuroretinopathy. Methods: Case report. Clinical and imaging data from a patient with acute macular neuroretinopathy were reviewed. Imaging comprised infrared scanning laser ophthalmoscopy, optical coherence tomography and flood-illumination adaptive optics images acquired through different entry pupils in the cardinal directions (approximately 2° eccentricity). Results: The patient reported acute bilateral paracentral scotoma revealing dark, wedge-shaped macular plaques which by optical coherence tomography were associated with focal loss of the visibility of the cone outer segment tip and inner/outer segment lines. Comparing scanning laser ophthalmoscopy images taken at different entry points in the pupil showed that macular plaques varied from hyporeflectance to isoreflectance. Cone counts by flood-illumination adaptive optics within plaques and optical coherence tomography features of the cone outer segment tip showed also a strong directional variability, peaking at near-normal values. Within each modality, fusion images showed that directional variability covered most of macular plaques. Conclusion: The characteristic fundus abnormalities of acute macular neuroretinopathy may show a strong directional variability. Our findings suggest that the Stiles–Crawford effect may be an important factor in signs and symptoms of acute macular neuroretinopathy. Abstract : In a case of acute macular neuroretinopathy, significant variability of fundus features were observed using infrared scanning laser ophthalmoscopy images, optical coherence tomography, and adaptive-optics en face images when taking images through different point of entry in the pupil. This suggests that photoreceptors mispointing or disarray may be present in acute macular neuroretinopathy, and hence that the Stiles–Crawford effect contributes to fundus features.